Metalloproteinases (MMPs) in hypertensive disorders: role, function, pharmacology, and potential strategies to mitigate pathophysiological changes - Soroush Taherkhani; Mohammad Sheibani; Mohammad Sheibani; Ali Mohammadkhanizadeh; Jitka A. I. Virag; Lisandra de Castro Braz; Yaser Azizi (Frontiers in Pharmacology)
Matrix metalloproteinases (MMPs) are a family of enzymes that play an important role in the pathophysiology of hypertensive disorders, particularly through their involvement in extracellular matrix (ECM) remodeling and vascular dysfunction. Their activity is closely linked to hypertension-mediated organ damage, which affects the vascular and cardio-renal systems. MMPs are responsible for degrading various components of the ECM, which is crucial for maintaining vascular structure and function. In hypertensive patients, several MMPs, including MMP-1, MMP-3, and MMP-9, are often found at elevated levels. This is associated with vascular remodeling and dysfunction due to chronic high blood pressure. The activation of MMPs in hypertension can be triggered by several factors, such as oxidative stress, inflammatory cytokines, and vasoactive agents like angiotensin II. In addition to increasing MMP activity, these variables cause an imbalance between MMPs and tissue inhibitors of metalloproteinases (TIMPs), which are the MMPs’ natural inhibitors. This imbalance contributes to excessive degradation of the ECM and promotes pathological changes in vascular smooth muscle cells (VSMCs), leading to their transition from a contractile to a synthetic phenotype. This shift facilitates cell growth and migration, exacerbating vascular remodeling. Given their critical roles in hypertension-related organ damage, MMPs are being explored as potential pharmacological targets. Inhibitors of MMPs may help mitigate the adverse effects of hypertension by restoring balance in ECM remodeling processes. Understanding their mechanisms opens avenues for targeted therapies that could significantly improve outcomes for individuals suffering from hypertension-related complications.